Brain imaging in mitochondrial respiratory chain deficiency: combination of brain MRI features as a useful tool for genotype/phenotype correlations. Issue 7 (1st May 2014) - Bricout, M; Grévent, D; Lebre, A S; Rio, M; Desguerre, I; De Lonlay, P; Valayannopoulos, V; Brunelle, F; Rötig, A; Munnich, A; Boddaert, N
Abstract : Mitochondrial diseases are characterised by a broad clinical and genetic heterogeneity that makes diagnosis difficult. Owing to the wide pattern of symptoms in mitochondrial disorders and the constantly growing number of disease genes, their genetic diagnosis is difficult and genotype/phenotype correlations remain elusive. Brain MRI appears as a useful tool for genotype/phenotype correlations. Here, we summarise the various combinations of MRI lesions observed in the most frequent mitochondrial respiratory chain deficiencies so as to direct molecular genetic test in patients at risk of such diseases. We believe that the combination of brain MRI features is of value to support respiratory chain deficiency and direct molecular genetic tests.